Media Framing of Restrictions on the Right of American Transgender Groups: A Case Study on Middle Eastern News Coverage - Aulia, Aldila Zulfa Nur (EKSPRESI DAN PERSEPSI : JURNAL ILMU KOMUNIKASI, 2025)
Over the past decade, the United States has experienced a significant and consistent increase in the number of individuals identifying as transgender. According to data from 2013, approximately 3.5% of Americans identified as transgender, whereas by 2022, this figure had risen to 7.2%, representing an estimated 20 million individuals. The U.S. government has implemented a series of policies that restrict the rights of transgender groups, as depicted in media coverage. This research aims to analyze the framing differences in news articles regarding restrictions on the rights of transgender groups following Executive Orders No. 14168, 14173, 14183, and 14201. Moreover, this study draws on data from Al Jazeera and Al Arabiya by analyzing three news articles from each outlet, employing Robert M. Entman's framing analysis. The study found that Al Jazeera emphasized the social aspect of the issue and advocated for the protection of vulnerable groups. In contrast, Al Arabiya framed the issue from a more sociological perspective, critically addressing topics that diverge from dominant traditional norms, particularly those related to politeness and the efficiency of public institutions. This framing reflects Al Arabiya's comparatively conservative orientation, characterized by its critique of gender ideology. The different analysis results show that the way each media form frames is based on its cultural and ideological orientation.